On the homotopy perturbation method for Boussinesq-like equations - Fernández, Francisco Marcelo (2014)
We comment on some analytical solutions to a class of Boussine sq-like equations derived recently by means of the homotopy perturbation method (HPM). We show that one may obtain exactly the same result by means of the Taylor series in the time variable. We derive more general results by means of traveling waves and argue that a curious superposition principle proposed by the author may not be of any mathematical or physical significance.